Comparitive study of natural and commercial pectin on the growth of probiotic - Chatterjee, Emon; Manuel, Suba GA; Hasan, Syed Shamimul (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The search for functional foods or functional food ingredients that can enhance health, is one ofthe leading trends in today’s food industry (Saarela et al.,2002). In this context, probiotics andprebiotics receive much attention. Functional foods or functional food ingredients exert abeneficial effect on host health and/or reduce the risk of chronic disease beyond their nutritivevalue. A food can be made functional by addition of a potential health promoting entity, reducingor removing concentrations of harmful components and/or modifying the nature or thebioavailability of one or more components. The first generation of functional foods was based onenrichment/ fortification with vitamins and minerals (mainly calcium). However, the concept hasrecently moved towards food ingredients exerting a positive effect on the gut microbiota,introducing probiotics and prebiotics (Christina 2007).